2019
DOI: 10.1097/dss.0000000000001662
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of Preoperative Topical Decolonization to Reduce Surgical Site Infection for Staphylococcus aureus Nasal Swab–Negative Mohs Micrographic Surgery Patients

Abstract: BACKGROUND Surgical site infection (SSI) is mainly due to endogenous bacteria. Topical decolonization is a preoperative intervention currently advised for proven nasal carriers of Staphylococcus aureus (S. aureus). OBJECTIVE The authors assessed whether topical decolonization could be of benefit for patients who are not nasal carriers of S. aureus. METHODS AND MATERIALS The authors performed a randomized con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 10 publications
0
23
0
1
Order By: Relevance
“…The remaining 30 studies were subjected to full-text review to exclude those with irrelevant subjects or those that did not fully meet the inclusion criteria. Ultimately, 20 studies were included in the meta-analyses [ 12 31 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 30 studies were subjected to full-text review to exclude those with irrelevant subjects or those that did not fully meet the inclusion criteria. Ultimately, 20 studies were included in the meta-analyses [ 12 31 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The pooled results from 20 studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] accounting of 10,526 patients showed that nasal decolonization may be associated with a significantly decreased risk of overall SSI in patients after surgery (RR = 0.59, 95% CI Tang et al Ann Clin Microbiol Antimicrob (2020) 19:33 Fig. 3).…”
Section: Nasal Decolonization and The Risk Of Overall Ssis After Surgerymentioning
confidence: 99%
“…The characteristics of the included studies are presented in Table 1. The studies were published between 1996 and 2019 and performed in the United States 14,17,18,21,24,26 , Netherlands 16,[28][29][30] , and Australia 19,23,31 . Besides, the quality of included articles according to Cochrane's Book was shown in Figure 2.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…The pooled results from 20 studies [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] accounting of 10526 patients showed that nasal decolonization may be associated with a signi cantly decreased risk of overall SSI in patients after surgery (RR=0.59, 95% CI: 0.38−0.90; Figure 3). Random effects model was chosen to balance the statistical heterogeneity (p for Cochrane's Q test=0.000, I 2 =75.8%).…”
Section: Nasal Decolonization and The Risk Of Overall Ssis After Surgerymentioning
confidence: 99%
“…The decontamination regime for MSSA was largely adapted from MRSA. As a MSSA specific national recommendation is lacking, the decontamination protocol was created in accordance with relevant international publications and expertise of clinical hygienists [4,7,21,22].…”
Section: Patient Pathwaymentioning
confidence: 99%